Aminated graphene oxide / heterocyclic aramid composite fiber and preparation method thereof
By reacting amidated graphene oxide with heterocyclic aramid aramid aramid compound, a amineated graphene oxide/heterocyclic aramid composite fiber is formed, which solves the problem of uneven spinning caused by graphene agglomeration, improves the mechanical properties and stability of the fibers, and is suitable for actual production.
Patent Information
- Application Number
- CN202311272441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when graphene is introduced into heterocyclic aramid fibers, graphene agglomeration leads to uneven spinning, poor stability and mechanical properties, and it is difficult to use in actual production.
Agated graphene oxide dispersion is used to react with heterocyclic aramid aramid aramid compound to form agated graphene oxide/heterocyclic aramid composite fiber. It is prepared by wet spinning process to control the dispersion and polymerization of graphene, and improve the tensile and compressive properties of the fibers.
The tensile properties, compressive properties and interface properties of amidated graphene oxide/heterocyclic aramid composite fiber are improved, and the mechanical properties stability of the fiber in organic solvents is enhanced, which is suitable for actual production.
Smart Images

Figure CN119710961A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon materials, and specifically relates to an aminated graphene oxide / heterocyclic aramid composite fiber and a preparation method thereof. Background Art
[0002] Heteroaramid fiber is an organic high-performance fiber with excellent properties such as light weight, high strength, high modulus, and impact resistance. It has important applications in aerospace and defense industries such as engine casings of weapon systems, bulletproof helmets, and aircraft skins. In engineering applications, domestic heteroaramid fibers still face a large gap in mechanical properties compared to foreign ones, and their use areas are relatively limited. Therefore, how to develop a series of fiber products based on the structural weaknesses of heteroaramid fibers and the needs of actual application scenarios is the key to realizing the application of heteroaramid fibers. Graphene is composed of sp 2 Two-dimensional nanocarbon materials composed of hybrid carbon atoms arranged in a honeycomb-like structure have the characteristics of high strength, high modulus and high specific surface area, and are ideal structural reinforcement materials.
[0003] At present, some studies have introduced graphene into heterocyclic aramid fibers. For example, in Chinese invention patent CN202110977053.9, graphene materials are added to aramid polymer solution as graphene aramid spinning solution. However, direct mixing easily causes graphene agglomeration, making the aramid composite fibers obtained by spinning uneven, with poor stability and mechanical properties, making them difficult to use in actual production. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing aminated graphene oxide / heterocyclic aramid composite fibers, which specifically comprises the following steps:
[0005] (1) Preparation of aminated graphene oxide dispersion: dispersing graphene oxide in N,N-dimethylacetamide, adding a heterocyclic aramid aromatic amine compound, and heating to fully react to obtain an aminated graphene oxide dispersion;
[0006] (2) Preparation of aminated graphene oxide polymerization liquid: before the polymerization reaction occurs, adding the above graphene dispersion liquid into the polymerization reaction system to form an aminated graphene oxide polymerization liquid;
[0007] (3) The amino graphene oxide / heterocyclic aramid composite fiber is prepared by wet spinning.
[0008] According to a specific embodiment of the present invention, the heterocyclic aramid aromatic amine compound is selected from one or more of p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, 2-chloro-4,4-diaminobenzanilide, 3,4'-diaminobiphenyl ether, etc.; preferably p-phenylenediamine.
[0009] According to a specific embodiment of the present invention, the mass ratio of the graphene oxide to the heterocyclic aramid aromatic amine compound is 1:(1-3); preferably 1:(1-2).
[0010] According to a specific embodiment of the present invention, in step (1), the heating temperature is 50-100°C.
[0011] According to a specific embodiment of the present invention, the flake diameter of the graphene oxide material is 0.1 to 3 μm, preferably 0.1 to 0.3 μm.
[0012] According to a specific embodiment of the present invention, the carbon-oxygen ratio of the above-mentioned graphene oxide material is 2-5, and the number of layers is 1-5; preferably, the number of layers is 1-3.
[0013] According to a specific embodiment of the present invention, step (2) specifically includes the following steps: adding lithium chloride, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reaction kettle containing N,N-dimethylacetamide, and stirring under nitrogen until completely dissolved; after cooling, adding the aminated graphene oxide dispersion to the completely dissolved mixed solvent before the polymerization reaction occurs and stirring, adding terephthaloyl chloride in batches, stirring thoroughly, and obtaining an aminated graphene oxide / heterocyclic aramid polymerization solution.
[0014] According to a specific embodiment of the present invention, the above-mentioned cooling step specifically includes: lowering the temperature to -10 to 10°C.
[0015] According to a specific embodiment of the present invention, the stirring time after adding the aminated graphene oxide dispersion is 5-20 minutes; and / or, the sufficient stirring time is 5-8 hours.
[0016] According to a specific embodiment of the present invention, the above step (3) specifically includes the following steps: the aminated graphene oxide / heterocyclic aramid polymer solution is subjected to a spinning process to obtain primary fibers of heterocyclic aramid containing aminated graphene oxide, and then subjected to a secondary coagulation bath, water washing, and drying, and then subjected to a heat stretching treatment at a temperature of 360 to 400° C. and a nitrogen atmosphere, and finally rolled into aminated graphene oxide / heterocyclic aramid composite fibers.
[0017] According to a specific embodiment of the present invention, the preparation method of the above-mentioned primary fiber includes: vacuum degassing the amino graphene oxide / heterocyclic aramid polymer solution, and then evenly spraying it out from a spinneret, and then performing double diffusion and a certain stretching action in a primary coagulation bath to form the primary fiber.
[0018] According to a specific embodiment of the present invention, the mass percentage of graphene oxide in the aminated graphene oxide / heterocyclic aramid composite fiber is 0.01% to 1%, preferably 0.01% to 0.5%.
[0019] The second object of the present invention is to provide aminated graphene oxide / heterocyclic aramid composite fibers prepared by the above-mentioned preparation method.
[0020] Beneficial Effects
[0021] Compared with the method of directly adding graphene powder, the pre-prepared graphene dispersion can improve the dispersibility of graphene in the spinning solution to a certain extent (such as in Chinese invention patent CN202110419613.9, graphene oxide or amino graphene with carboxyl groups is dissolved in N,N-dimethylacetamide / lithium chloride composite solvent to obtain a graphene dispersion, and then aramid monomers p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, and terephthaloyl chloride are added to the graphene dispersion to obtain graphene aramid spinning solution). However, the inventors further found that the above method has the problem that lithium chloride in the composite solvent is prone to cause graphene agglomeration due to the salt ion effect. Therefore, the graphene dispersion cannot be stored for a long time and is only suitable for the preparation of spinning solution immediately after preparation, which brings many inconveniences to actual production. In this patent, aminated graphene is used to solve the dispersion problem of graphene. However, other impurities will be introduced during the preparation process of aminated graphene, which will have an adverse effect on the spinning of heterocyclic aramid. In addition, the complexity and danger of the preparation process of aminated graphene have seriously hindered industrial production.
[0022] The present invention firstly adopts heterocyclic aramid diamine monomer to prepare aminated graphene oxide as the initial raw material of polymerization reaction, which is convenient for industrial production. In the preparation process of aminated graphene oxide dispersion, no auxiliary agent (such as lithium chloride or calcium chloride) is added. Before the polymerization reaction occurs, the aminated graphene oxide dispersion is added to the polymerization reaction system, thereby improving the tensile properties, compressive properties and interface properties of the composite fiber, and improving the mechanical property stability in organic solvents such as DMSO, DMF, DMAc, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the synthesis mechanism of functionalized graphene;
[0024] Figure 2 This is an optical microscopic image of the aminated graphene oxide dispersion prepared in Example 1 with or without the addition of lithium chloride after being left to stand for 1 hour;
[0025] Figure 3 This is a diagram showing the swelling of the amino-modified graphene / aramid III composite fiber prepared in an example in an organic solvent;
[0026] Figure 4 Optical microscopy images of the polymerization liquids of Example 6 and Comparative Example 3 with different addition orders (dispersion status of aminated graphene oxide in the polymer). DETAILED DESCRIPTION
[0027] The following further exemplifies the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0028] The method for preparing the aminated graphene oxide / heterocyclic aramid composite fiber of the present invention specifically comprises: (1) preparing an aminated graphene oxide dispersion liquid: dispersing graphene oxide in N,N-dimethylacetamide, adding a heterocyclic aramid aromatic amine compound, and heating it to make it fully react to obtain an aminated graphene oxide dispersion liquid; (2) preparing an aminated graphene oxide polymer liquid: before the polymerization reaction occurs, adding the above-mentioned graphene dispersion liquid to a polymerization reaction system to form an aminated graphene oxide polymer liquid; (3) preparing the above-mentioned aminated graphene oxide / heterocyclic aramid composite fiber by wet spinning.
[0029] In step (1), the present invention directly uses heterocyclic aramid diamine monomers to aminate graphene oxide, and does not add metal salts such as lithium chloride and calcium chloride. The advantages of this method are: this dispersion can be directly used in experiments, there is no need to perform amination treatment on graphene separately, no impurities outside the system are introduced during the process, and the aminated graphene dispersion without metal salts is not easy to agglomerate and is easy to store, and does not require any additives.
[0030] In step (1), the heating temperature is 50-100° C.; the mass ratio of graphene oxide to heterocyclic aramid aromatic amine compound is 1:(1-3); preferably 1:(1-2).
[0031] The amount of diamine added and the reaction temperature are controlled to control the number of amine groups. In situ regulation of the number of amine groups can regulate the orientation of the molecular chain and the lateral force, taking into account the tensile mechanical properties, compressive properties and interface properties of the fiber.
[0032] Step (2) is specifically as follows: add metal salt cosolvent lithium chloride, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reaction kettle containing N,N-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is lowered to -10 to 10°C, the above-prepared aminated graphene oxide dispersion is added to the completely dissolved mixed solvent before the polymerization reaction occurs and stirred. The stirring time is 5-20 minutes, and terephthaloyl chloride is added in batches, and stirred for 5-8 hours to obtain an aminated graphene oxide / heterocyclic aramid polymerization solution.
[0033] Before the polymerization reaction occurs, the aminated graphene oxide composite solvent is added into a mixed solvent in which 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are completely dissolved in advance, and terephthaloyl chloride is added in batches after stirring for 5-20 minutes. The advantages are: firstly, by adopting the above-mentioned adding sequence, compared with adding the graphene oxide dispersion liquid at the same time or adding it during the polymerization process, 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are mixed with the graphene dispersion liquid in the form of a mixed solvent, which can effectively avoid the agglomeration of graphene oxide caused by solid-state, high-adhesion 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine; secondly, by simultaneously adding the aminated graphene oxide dispersion liquid to the pre-dissolved 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine / N,N-dimethylacetamide mixed solvent, the stirring time of graphene in the reactor can be reduced, and the aminated graphene oxide can be well dispersed in the composite solvent without agglomeration; in addition, the aminated graphene oxide is added before terephthaloyl chloride to participate in the polymerization process of the aramid monomer, so that the graphene oxide can be well dispersed in the polymer without agglomeration.
[0034] Step (3) is specifically as follows: vacuum degassing the aminated graphene oxide / heterocyclic aramid polymer solution, and then evenly spraying it out from the spinneret, passing through a primary coagulation bath for double diffusion and a certain stretching action to form primary fibers, and then passing through a secondary coagulation bath, washing, and drying, and then entering a temperature of 360 to 400° C. and a nitrogen atmosphere for heat stretching treatment, and finally winding it into an aminated graphene oxide / heterocyclic aramid composite fiber.
[0035] In the technical solution of the invention, the content of graphene in the graphene oxide / heterocyclic aramid composite fiber in the fiber matrix is controlled to be 0.01% to 1%, preferably 0.01% to 0.5%. For example, the content can be 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%.
[0036] If the amount of aminated graphene oxide added exceeds a certain limit, the dispersibility of the aminated graphene oxide in the composite polymer solution will decrease, which will lead to unbalanced mechanical properties of the composite fiber. The present invention controls the aminated graphene oxide within the above range, which is conducive to the uniform dispersion of the aminated graphene oxide in the polymer.
[0037] Example 1
[0038] (1) Preparation of aminated graphene oxide dispersion:
[0039] Graphene oxide (carbon-oxygen ratio 3, number of layers 1-3, flake diameter 300 nm) was dispersed in N,N-dimethylacetamide, and p-phenylenediamine (graphene oxide: p-phenylenediamine = 1:1) was added, followed by heating at 90°C under a nitrogen atmosphere to allow it to react fully to obtain a uniform and stable aminated graphene oxide dispersion.
[0040] (2) Preparation of aminated graphene oxide polymer solution:
[0041] Add LiCl, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing N,N-dimethylacetamide, and stir under nitrogen until completely dissolved. Lower the temperature to 10°C, and add the aminated graphene oxide dispersion prepared in 1 above to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir. Stir for 5-20 minutes, add terephthaloyl chloride in batches, and stir thoroughly for 5-8 hours to obtain an aminated graphene oxide / heterocyclic aramid polymerization solution.
[0042] (3) Preparation of aminated graphene oxide / heterocyclic aramid composite fibers:
[0043] The aminated graphene oxide / heterocyclic aramid polymer solution was vacuum degassed, and then uniformly ejected from the spinneret, and then double-diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched at 400°C in a nitrogen atmosphere, and finally rolled into aminated graphene oxide / heterocyclic aramid composite fibers. The tensile strength of the composite fiber was measured to be 35.14 cN / dtex. Among them, the aminated graphene oxide accounted for 0.01% of the fiber mass fraction.
[0044] Figure 1 The figure is a schematic diagram of the synthesis mechanism of functionalized graphene. In the figure, amine compounds (NH2≥2) are used as an example to explain the process of forming surface modification groups. It can be seen from the figure that p-phenylenediamine reacts with oxygen-containing groups on the surface of graphene oxide to connect to the graphene surface.
[0045] Figure 2The optical microscope images of the aminated graphene oxide dispersion prepared in Example 1 with or without the addition of lithium chloride after standing for 1 hour. As shown in the figure, the aminated graphene oxide composite solvent without the addition of lithium chloride has no aggregated large particles under the optical microscope after one day, and the aminated graphene oxide is dispersed in the N, N-dimethylacetamide / lithium chloride composite solvent, and there are many large particle agglomerations under the optical microscope after one day.
[0046] Figure 3 ① is the swelling diagram of the aminated graphene oxide / aramid III composite fiber prepared in Example 1 in the organic solvent DMAc, Figure 3 ② is a swelling diagram of heterocyclic aramid in organic solvent DMAc. As shown in the figure, heterocyclic aramid is completely swollen in organic solvent DMAc after 1 hour, while aminated graphene oxide modified aramid is not completely swollen in organic solvent DMAc. It can be seen that the composite fiber obtained by adopting the technical solution of the present application has better stability in organic solvent DMAc.
[0047] Example 2
[0048] The other steps and parameters are the same as those in Example 1, except that the ratio of graphene oxide to p-phenylenediamine is 1:2. The tensile strength of the composite fiber is measured to be 34.34 cN / dtex.
[0049] Example 3
[0050] The other steps and parameters are the same as those in Example 1, except that the heating temperature in step (1) is 60°C.
[0051] The tensile strength of the composite fiber was measured to be 34.76 cN / dtex.
[0052] Example 4
[0053] The other steps and parameters are the same as those in Example 1, and the mass fraction of the aminated graphene oxide powder in the fiber mass fraction is adjusted to 0.1%.
[0054] The tensile strength of the composite fiber was measured to be 35.37 cN / dtex.
[0055] Example 5
[0056] The other steps and parameters are the same as those in Example 1, and the mass fraction of the aminated graphene oxide powder in the fiber mass fraction is adjusted to 0.2%;
[0057] The tensile strength of the composite fiber was measured to be 37.42 cN / dtex.
[0058] Example 6
[0059] The other steps and parameters are the same as those in Example 1, and the mass fraction of the aminated graphene oxide powder in the fiber mass fraction is adjusted to 0.3%;
[0060] The tensile strength of the composite fiber was measured to be 38.85 cN / dtex, the compressive strength was 760 MPa, and the interfacial shear strength was 53 MPa.
[0061] Example 7
[0062] The other steps and parameters are the same as those in Example 1, and the mass fraction of the aminated graphene oxide powder in the fiber mass fraction is adjusted to 0.5%;
[0063] The tensile strength of the composite fiber was measured to be 35.67 cN / dtex.
[0064] Example 8
[0065] The other steps and parameters are the same as those in Example 1, and the mass fraction of the aminated graphene oxide powder in the fiber mass fraction is adjusted to 1%;
[0066] The tensile strength of the composite fiber was measured to be 34.25 cN / dtex.
[0067] Comparative Example 1
[0068] The other steps and parameters are the same as those in Example 6, except that, in step (1), the dispersion liquid of the aminated graphene oxide powder adopts N,N'-dimethylacetamide / lithium chloride composite solvent;
[0069] By comparison, it can be seen that graphene agglomeration is obviously present in the polymerization solution, the mechanical properties of the fiber show a downward trend, and the tensile strength of the composite fiber is measured to be 32.37 cN / dtex.
[0070] Comparative Example 2
[0071] The other steps and parameters are the same as those in Example 6, except that in step (2), the aminated graphene oxide dispersion is added to the dissolved terephthaloyl chloride solution, and then other diamine monomers are added.
[0072] By comparison, it can be seen that graphene agglomeration is obviously present in the polymer solution, the mechanical properties of the fiber show a downward trend, and the tensile strength of the composite fiber is measured to be 29.73 cN / dtex.
[0073] Comparative Example 3
[0074] The other steps and parameters are the same as those in Example 6, except that in step (2), the aminated graphene oxide dispersion is added to the solution of dissolved p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole, and then terephthaloyl chloride is added.
[0075] By comparison, it can be seen that graphene agglomeration is obviously present in the polymer solution, the mechanical properties of the fiber show a downward trend, and the tensile strength of the composite fiber is measured to be 32.83 cN / dtex.
[0076] Figure 4 The optical microscope images of the polymerization liquid (dispersion of aminated graphene oxide in polymer) of different addition orders of Example 6 and Comparative Example 3 are shown. As shown in the figure, when the aminated graphene oxide dispersion liquid is added to the dissolved diamine monomer solution, no large particles exist in the polymerization liquid after the polymerization is completed; when the dissolved diamine monomer solution is added to the aminated graphene oxide dispersion liquid, particles agglomerate in the polymerization liquid after the polymerization is completed; when the dissolved terephthaloyl chloride solution is added to the aminated graphene oxide and diamine monomer solution, particles agglomerate in the polymerization liquid after the polymerization is completed.
[0077] The tensile strength parameters of various embodiments and comparative examples are summarized in Table 1.
[0078] Table 1
[0079] Tensile strength (cN / dtex) Example 1 35.14 Example 2 34.34 Example 3 34.76 Example 4 35.37 Example 5 37.42 Example 6 38.85 Example 7 35.67 Example 8 34.25 Comparative Example 1 32.37 Comparative Example 2 29.73 Comparative Example 3 32.83
[0080] By analyzing Comparative Example 1 and Example 6, it can be seen that when no additives such as lithium chloride are added to the graphene oxide dispersion, the mechanical properties of the obtained composite fiber are better. By analyzing Comparative Examples 2, 3 and Example 6, it can be found that by adopting the specific addition sequence of "adding the aminated graphene oxide dispersion to the polymerization reaction system before the polymerization reaction occurs" of the present application, the mechanical properties of the obtained composite fiber are better.
[0081] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0082] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A method for preparing aminated graphene oxide / heterocyclic aramid composite fiber, characterized in that: The specific steps include: (1) Preparation of aminated graphene oxide dispersion: dispersing graphene oxide in N,N-dimethylacetamide, adding a heterocyclic aramid aromatic amine compound, and heating to fully react to obtain an aminated graphene oxide dispersion; (2) Preparation of aminated graphene oxide polymerization liquid: before the polymerization reaction occurs, adding the graphene dispersion liquid into the polymerization reaction system to form an aminated graphene oxide polymerization liquid; (3) The amino graphene oxide / heterocyclic aramid composite fiber is prepared by wet spinning.
2. The preparation method according to claim 1, characterized in that: The heterocyclic aramid aromatic amine compound is selected from one or more of p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, 2-chloro-4,4-diaminobenzanilide, 3,4'-diaminobiphenyl ether, etc.; preferably p-phenylenediamine.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the graphene oxide to the heterocyclic aramid aromatic amine compound is 1:(1-3); preferably 1:(1-2).
4. The preparation method according to claim 1, characterized in that: In step (1), the heating temperature is 50-100°C.
5. The preparation method according to claim 1, characterized in that: The sheet diameter of the graphene oxide is 0.1 to 3 μm, preferably 0.1 to 0.3 μm.
6. The preparation method according to claim 1, characterized in that: The carbon-oxygen ratio of the graphene oxide material is 2-5, and the number of layers is 1-5; preferably, the number of layers is 1-3.
7. The preparation method according to claim 1, characterized in that: Step (2) specifically includes the following steps: adding lithium chloride, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reaction kettle containing N,N-dimethylacetamide, and stirring under nitrogen until completely dissolved; after cooling, adding the aminated graphene oxide dispersion liquid to the completely dissolved mixed solvent before the polymerization reaction occurs and stirring, adding terephthaloyl chloride in batches, stirring thoroughly, and obtaining an aminated graphene oxide / heterocyclic aramid polymerization liquid.
8. The preparation method according to claim 6, characterized in that: The cooling step specifically includes: lowering the temperature to -10 to 10°C.
9. The preparation method according to claim 1, characterized in that: The step (3) specifically comprises the following steps: subjecting the aminated graphene oxide / heterocyclic aramid polymer solution to a spinning process to obtain primary fibers of heterocyclic aramid containing aminated graphene oxide, and then subjecting the fibers to a secondary coagulation bath, water washing, and drying, and then subjecting the fibers to a heat stretching treatment at a temperature of 360 to 400° C. and a nitrogen atmosphere, and finally winding the fibers into aminated graphene oxide / heterocyclic aramid composite fibers.
10. The preparation method according to claim 1, characterized in that: The mass percentage of graphene oxide in the aminated graphene oxide / heterocyclic aramid composite fiber is 0.01-1%, preferably 0.01-0.5%.
11. Aminated graphene oxide / heterocyclic aramid composite fiber prepared according to the preparation method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Graphene high-strength impact-resistant aramid fiber and preparation method thereof
CN113718364A
A method for preparing graphene-modified high-strength, high-modulus heterocyclic aramid fibers
CN115216857B
High-strength conductive aramid fiber core material and forming process thereof
CN112812373A
Olefinic carbon material dispersion liquid and application thereof
CN113248739A
Graphene modified polyamide 6 composite fiber material and preparation method thereof
CN115449916A
Cited By
Preparation of bulk modified graphene and diaphragm method
CN120698449A
